Preparation method of impact-resistant and high-wear-resistant PE film

By combining POSS and graphene and melting and grafting with polyethylene, the problem of insufficient mechanical properties of PE films in special occasions is solved, which significantly improves impact, wear and anti-static properties, and meets higher packaging protection Membrane performance requirements.

CN119463239AInactive Publication Date: 2025-02-18HUBEI JIANHAI EMERGING MATERIALS CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411591256.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-08
Publication Date
2025-02-18
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

In some special occasions, the existing PE films have insufficient mechanical properties and are prone to fracture and damage, have average wear resistance, poor impact resistance, and are prone to accumulation of static electricity, affecting the application range.

Method used

POSS and graphene are effectively combined through chemical grafting, and an alkenyl structure is introduced to produce melt graft with polyethylene, improving compatibility, enhancing the impact and wear resistance of the PE film, and at the same time improving the anti-static properties.

Benefits of technology

The prepared PE film has excellent impact resistance and high wear resistance, and significantly improves antistatic properties, meeting higher packaging protective film performance requirements.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005125648740000061
    Figure BDA0005125648740000061
  • Figure BDA0005125648740000121
    Figure BDA0005125648740000121
Patent Text Reader

Abstract

The invention relates to the technical field of PE (polyethylene) protective films, and discloses a preparation method of an impact-resistant high-wear-resistant PE film, diamine POSS (polyhedral oligomeric silsesquioxane), trans-4-hydroxycinnamic acid, 4-bromophthalic anhydride and the like are used as raw materials, chemical bonding is generated by utilizing maleic anhydride groups in the structure of the raw materials and oxygen-containing groups on the surface of graphene oxide through condensation and substitution reactions, and the impact-resistant high-wear-resistant PE film is prepared. Carrying out melt grafting with linear low-density polyethylene, and carrying out blow molding to obtain a PE film; the alkenyl of the alkenyl graphene grafted POSS can generate a grafting reaction with a polyethylene matrix, so that the compatibility between the alkenyl graphene grafted POSS and the polyethylene matrix is improved, massive agglomeration of inorganic particles is avoided, and the inorganic particles are uniformly dispersed in the PE matrix; the rigid inorganic cage-shaped core in the POSS structure has relatively high hardness and can effectively resist external scraping and abrasion; the honeycomb structure of graphene can restrain the expansion and extension of microcracks, enhance the impact resistance, and further improve the antistatic and barrier properties of the PE film.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of PE protective films, in particular to a method for preparing an impact-resistant and highly wear-resistant PE film. Background Art

[0002] PE (polyethylene) is a thermoplastic resin with a simple structure, good heat sealing, transparency and certain barrier properties. With the continuous progress of society, PE film has been widely used in composite packaging in the pharmaceutical, chemical, food, electronics, printing and other industries. However, with the development of the times, the market has put forward higher and higher requirements on the performance of PE film. The existing PE film cannot meet the performance requirements of packaging protective film in some special occasions. Under certain conditions, traditional polyethylene film is prone to breakage due to mechanical properties that do not meet the requirements, and has general wear resistance and poor impact resistance. Therefore, simple PE film is far from meeting the needs of social development. Moreover, since the polyethylene matrix is ​​prone to accumulate static electricity during use, it affects its application range. Therefore, improving the mechanical properties and wear resistance of polyethylene film has become a research focus.

[0003] The prior art generally achieves the purpose of modifying PE film by adding fillers to polyethylene, but the modification effect of conventional ordinary fillers is not obvious. Only when the filler particles are reduced to nanometer size, the physical properties of the material will suddenly change. However, a small amount of fillers cannot improve the mechanical properties, and a large amount of fillers will cause problems such as uneven dispersion and easy agglomeration. Patent No. CN107987360A discloses a high-toughness and impact-resistant PE film and a preparation method thereof. The formula includes: low-density polyethylene, metallocene linear low-density polyethylene, medium-density polyethylene, polyvinyl butyral, erucic acid amide, antioxidant, sodium rosin acid, calcium-zinc composite stabilizer, nano titanium dioxide and cellulose acetate and other raw materials. By improving the formula and optimizing the process, the prepared PE film has good toughness and impact resistance, but the formula components are too many, the preparation process is complicated, and the wear resistance of the PE film is not improved.

[0004] POSS (cage-type polysilsesquioxane) is a nanomaterial with an organic-inorganic hybrid core-shell structure, with a hexahedral cage structure composed of Si-O-Si bonds as the inorganic framework core, which can be used as an anti-wear agent, thereby improving the wear resistance of PE film; due to its own high aspect ratio, graphene is stable to small molecules such as water, and has the characteristics of high specific surface area and adjustable morphology. It is easier to form a skeleton in a polymer matrix, which is significantly helpful for improving the mechanical properties of the material; the present invention aims to effectively combine POSS and graphene by chemical grafting, introduce an olefinic structure, and then produce melt grafting with polyethylene, improve the compatibility with polyethylene, and give play to the unique role of the synergistic reinforcing phase between the two, so that the prepared PE film has excellent impact resistance and high wear resistance, and further improves the antistatic property of the PE film. Summary of the invention

[0005] In view of this, the object of the present invention is to provide a method for preparing an impact-resistant and highly wear-resistant PE film. The Si-O-Si inorganic cage skeleton based on POSS has good wear resistance, and the 2D structure of graphene has excellent impact resistance. The synergistic effect of the two significantly improves the impact resistance and wear resistance of the PE film.

[0006] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:

[0007] A method for preparing an impact-resistant and highly wear-resistant PE film is carried out according to the following steps:

[0008] Step (1), adding graphene oxide and N,N-dimethylformamide into a reaction flask, ultrasonically dispersing for 1-3 hours, adding maleic anhydride olefinic POSS, reacting at 75-90° C. for 2-5 hours, filtering after the reaction, washing with ethanol, and freeze-drying to obtain olefinic graphene grafted POSS.

[0009] Step (2), vacuum-drying the linear low-density polyethylene and the metallocene polyethylene and placing them in a high-speed mixer, adding olefinic graphene grafted POSS, an antioxidant and a thermal stabilizer, and evenly dispersing them at a stirring speed of 800-1200 r / min and a temperature of 85-100° C., placing them in a twin-screw extruder, performing melt extrusion granulation, and then placing them in a film blowing machine for blow molding to obtain an impact-resistant and highly wear-resistant PE film.

[0010] Furthermore, in step (1), the mass ratio of graphene oxide to maleic anhydride-based POSS is 100:(30-50).

[0011] Furthermore, in step (2), the mass ratio of linear low density polyethylene, metallocene polyethylene, and olefinic graphene grafted POSS is (65-80):(20-35):(2-10).

[0012] Furthermore, in step (2), the feed port temperature of the twin-screw extruder is 90-100°C, the front section temperature is 130-140°C, the middle section temperature is 140-150°C, the rear section temperature is 160-170°C, and the die head temperature is 160-180°C.

[0013] Further, the preparation method of maleic anhydride alkenyl POSS in step (1) is carried out according to the following steps:

[0014] Step S1, under a nitrogen atmosphere, add diamine POSS, trans-4-hydroxycinnamic acid and N,N-dimethylformamide to a reaction flask, stir evenly, add 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride, 1-hydroxybenzotriazole and triethylamine, stir to react, after the reaction is completed, add dichloromethane and deionized water for extraction, concentrate the organic phase, and dry to obtain diol vinyl POSS.

[0015] Step S2, under a nitrogen atmosphere, add diol alkenyl POSS and N-methylpyrrolidone to a reaction flask, stir evenly, add 4-bromophthalic anhydride and cesium carbonate, stir to react, after the reaction is completed, cool to room temperature, extract with ethyl acetate and deionized water, concentrate the organic phase, and dry to obtain maleic anhydride alkenyl POSS.

[0016] Furthermore, in step S1, the molar ratio of diamine POSS, trans-4-hydroxycinnamic acid, 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride, 1-hydroxybenzotriazole, and triethylamine is 1:(2.05-2.2):(2.1-2.4):(1.5-1.8):(3.1-3.3).

[0017] Furthermore, in step S1, the reaction temperature is 80-100° C., and the reaction time is 12-24 h.

[0018] Furthermore, in step S1, the molar ratio of diol alkenyl POSS, 4-bromophthalic anhydride and cesium carbonate is 1:(2.15-2.3):(2.5-2.8).

[0019] Furthermore, in step S2, the reaction temperature is 55-70° C., and the reaction time is 8-16 h.

[0020] Compared with the prior art, the present invention has the following beneficial effects:

[0021] The invention uses diamine POSS, trans-4-hydroxycinnamic acid, 4-bromophthalic anhydride and the like as raw materials, obtains maleic anhydride alkenyl POSS through condensation and substitution reaction, utilizes maleic anhydride groups in the structure and oxygen-containing groups on the surface of graphene oxide to generate chemical bonding, obtains alkenyl graphene grafted POSS, and finally melt-grafts with linear low-density polyethylene and metallocene polyethylene, and blows the resulting products to obtain an impact-resistant and highly wear-resistant PE film.

[0022] The olefinic group of olefinic graphene grafted POSS can produce a grafting reaction with the polyethylene matrix, improve the compatibility between the two, avoid the large-scale agglomeration of inorganic particles, and make them evenly dispersed in the PE matrix; the rigid inorganic cage core formed by the silicon-oxygen bonds in the POSS structure has a high hardness, can effectively resist external scratches and wear, keep the surface of the material flat and smooth, and enable the surface of the PE film to form a stable lubricating film when it is rubbed, thereby reducing the amount of wear and improving wear resistance.

[0023] Graphene itself has good mechanical properties. When the anhydride groups of maleic anhydride-olefinic POSS undergo esterification reaction with the oxygen-containing groups of graphene oxide, they are grafted to the surface of graphene through chemical bonds, which increases the spacing between graphene sheets and effectively avoids stacking. This allows graphene to be well dispersed in the PE matrix. When impacted, the honeycomb structure of graphene can further attenuate the impact force to constrain the expansion and extension of microcracks, absorb energy, reduce stress concentration in the PE matrix, and better maintain the stability of the structure.

[0024] Graphene oxide can chemically bond with the maleic anhydride group of maleic anhydride olefinic POSS and cross-link with polyethylene through the olefinic group in its structure. The increase in the degree of cross-linking allows graphene to adhere to the veins of the cross-linked network, forming a relatively complete graphene conductive pathway, improving the interface compatibility, and enhancing the antistatic properties of the PE film. At the same time, the lamellar structure of graphene has good dispersion in the PE matrix, resulting in the obstruction of the path of water molecules or other pollutants through the PE film, thereby improving the barrier properties of the PE film. DETAILED DESCRIPTION

[0025] The technical scheme in the embodiment of the present invention will be clearly and completely described below. Obviously, the described embodiment is only a part of the embodiment of the present invention, rather than all the embodiments. Based on the embodiments in the present invention, all other embodiments obtained by those of ordinary skill in the art without making creative work are within the scope of protection of the present invention. Unless otherwise specified, the raw materials and reagents used in this application are all commercially available products, or can be prepared by known methods.

[0026] Preparation of diamine POSS: 211 mL of ethanol, 9 mL of deionized water and 0.5 g of tetraethylammonium hydroxide were added to a reaction flask, and after stirring, 5.48 mL of phenyltriethoxysilane and 13.23 mL of (3-aminopropyl)triethoxysilane were added, and heated to reflux for 48 h to obtain a uniform transparent solution, which was concentrated under reduced pressure, filtered, washed with tetrahydrofuran, methanol and deionized water in turn, and dried to obtain diamine POSS (structural formula: ).

[0027] Preparation of graphene oxide: Weigh 2g of graphite powder and 70mL of concentrated sulfuric acid into a three-necked flask, stir and mix evenly under an ice bath, slowly add 12g of potassium permanganate to the mixture, stir at 40°C for 4h, then heat to 90°C and keep for 1h, add 250mL of deionized water and 30mL of hydrogen peroxide, let stand, centrifuge the product for 10min, wash with 5% hydrochloric acid solution 3-4 times, wash repeatedly with deionized water, and freeze-dry to obtain graphene oxide.

[0028] Trans-4-hydroxycinnamic acid, CAS number is 501-98-4.

[0029] 1-Ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride (EDCI), CAS number is 7084-11-9.

[0030] 1-Hydroxybenzotriazole (HOBT), CAS number is 2592-95-2.

[0031] 4-Bromophthalic anhydride, CAS number is 86-90-8.

[0032] Example 1

[0033] (1) Under nitrogen atmosphere, 80 mmol of diamine POSS, 168 mmol of trans-4-hydroxycinnamic acid and 520 mL of N,N-dimethylformamide were added to a reaction flask. After stirring, 180 mmol of 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride, 132 mmol of 1-hydroxybenzotriazole and 255 mmol of triethylamine were added. The mixture was reacted at 90 °C for 16 h. Dichloromethane and deionized water were added for extraction. The organic phase was concentrated and dried to obtain diol vinyl POSS.

[0034] (2) Under nitrogen atmosphere, 75 mmol of diol vinyl POSS and 900 mL of N-methylpyrrolidone were added to a reaction flask, and after stirring, 165 mmol of 4-bromophthalic anhydride and 202.5 mmol of cesium carbonate were added, and the mixture was reacted at 65° C. for 12 h, cooled to room temperature, extracted with ethyl acetate and deionized water, and the organic phase was concentrated and dried to obtain maleic anhydride vinyl POSS. The preparation reaction formula is as follows:

[0035]

[0036] (3) Add 15 g of graphene oxide and 330 mL of N,N-dimethylformamide into a reaction flask, ultrasonically disperse for 2 h, add 4.5 g of maleic anhydride olefinic POSS, react at 80 °C for 4 h, filter after the reaction, wash with ethanol, and freeze-dry to obtain olefinic graphene grafted POSS.

[0037] (4) 80 g of linear low-density polyethylene and 20 g of metallocene polyethylene were vacuum dried and placed in a high-speed mixer, 2 g of olefin-grafted graphene POSS, 1.2 g of antioxidant 1010 and 0.5 g of thermal stabilizer zinc stearate were added, and the mixture was evenly dispersed at a stirring speed of 1000 r / min and a temperature of 95° C. The mixture was placed in a twin-screw extruder with a feed inlet temperature of 95° C., a front section temperature of 135° C., a middle section temperature of 145° C., a rear section temperature of 165° C. and a die head temperature of 170° C. for melt extrusion granulation, and then placed in a film blowing machine for blow molding to obtain an impact-resistant and highly wear-resistant PE film.

[0038] Example 2

[0039] (1) Under nitrogen atmosphere, 120 mmol of diamine POSS, 246 mmol of trans-4-hydroxycinnamic acid and 600 mL of N,N-dimethylformamide were added to a reaction flask. After stirring, 252 mmol of 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride, 180 mmol of 1-hydroxybenzotriazole and 372 mmol of triethylamine were added. The mixture was reacted at 100 °C for 12 h. Dichloromethane and deionized water were added for extraction. The organic phase was concentrated and dried to obtain diol vinyl POSS.

[0040] (2) Under nitrogen atmosphere, 110 mmol of diol alkenyl POSS and 1100 mL of N-methylpyrrolidone were added to a reaction flask, and after stirring, 236.5 mmol of 4-bromophthalic anhydride and 275 mmol of cesium carbonate were added, and the mixture was reacted at 70 °C for 8 h. The mixture was cooled to room temperature, extracted with ethyl acetate and deionized water, and the organic phase was concentrated and dried to obtain maleic anhydride alkenyl POSS.

[0041] (3) Add 35 g of graphene oxide and 630 mL of N,N-dimethylformamide into a reaction flask, ultrasonically disperse for 1 h, add 12.25 g of maleic anhydride olefinic POSS, react at 90 °C for 2 h, filter after the reaction, wash with ethanol, and freeze-dry to obtain olefinic graphene grafted POSS.

[0042] (4) 75 g of linear low-density polyethylene and 25 g of metallocene polyethylene were vacuum dried and placed in a high-speed mixer, 4 g of olefin-grafted graphene POSS, 1.2 g of antioxidant 1010 and 0.5 g of thermal stabilizer zinc stearate were added, and the mixture was uniformly dispersed at a stirring speed of 1200 r / min and a temperature of 100° C. The mixture was placed in a twin-screw extruder with a feed inlet temperature of 100° C., a front section temperature of 140° C., a middle section temperature of 150° C., a rear section temperature of 170° C. and a die head temperature of 180° C. for melt extrusion granulation, and then placed in a film blowing machine for blow molding to obtain an impact-resistant and highly wear-resistant PE film.

[0043] Example 3

[0044] (1) Under nitrogen atmosphere, 45 mmol of diamine POSS, 99 mmol of trans-4-hydroxycinnamic acid and 360 mL of N,N-dimethylformamide were added to a reaction flask. After stirring, 108 mmol of 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride, 81 mmol of 1-hydroxybenzotriazole and 148.5 mmol of triethylamine were added. The mixture was reacted at 80 °C for 24 h. Dichloromethane and deionized water were added for extraction. The organic phase was concentrated and dried to obtain diol vinyl POSS.

[0045] (2) Under nitrogen atmosphere, 42 mmol of diol vinyl POSS and 630 mL of N-methylpyrrolidone were added to a reaction flask. After stirring, 138.6 mmol of 4-bromophthalic anhydride and 117.6 mmol of cesium carbonate were added. The mixture was reacted at 55 °C for 16 h. The mixture was cooled to room temperature, extracted with ethyl acetate and deionized water, and the organic phase was concentrated and dried to obtain maleic anhydride vinyl POSS.

[0046] (3) Add 20 g of graphene oxide and 360 mL of N,N-dimethylformamide into a reaction flask, ultrasonically disperse for 3 h, add 8 g of maleic anhydride olefinic POSS, react at 75 °C for 5 h, filter after the reaction, wash with ethanol, and freeze-dry to obtain olefinic graphene grafted POSS.

[0047] (4) 70 g of linear low-density polyethylene and 30 g of metallocene polyethylene were vacuum dried and placed in a high-speed mixer, 6 g of olefin-grafted graphene POSS, 1.2 g of antioxidant 1010 and 0.5 g of thermal stabilizer zinc stearate were added, and the mixture was evenly dispersed at a stirring speed of 800 r / min and a temperature of 85° C. The mixture was placed in a twin-screw extruder with a feed inlet temperature of 90° C., a front section temperature of 130° C., a middle section temperature of 140° C., a rear section temperature of 160° C. and a die head temperature of 160° C. for melt extrusion granulation, and then placed in a film blowing machine for blow molding to obtain an impact-resistant and highly wear-resistant PE film.

[0048] Example 4

[0049] (1) Under nitrogen atmosphere, 35 mmol of diamine POSS, 74.2 mmol of trans-4-hydroxycinnamic acid and 265 mL of N,N-dimethylformamide were added to a reaction flask. After stirring, 78.4 mmol of 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride, 58.8 mmol of 1-hydroxybenzotriazole and 112 mmol of triethylamine were added. The mixture was reacted at 95 °C for 15 h. Dichloromethane and deionized water were added for extraction. The organic phase was concentrated and dried to obtain diol vinyl POSS.

[0050] (2) Under nitrogen atmosphere, 30 mmol of diol vinyl POSS and 420 mL of N-methylpyrrolidone were added to a reaction flask. After stirring, 65.4 mmol of 4-bromophthalic anhydride and 79.5 mmol of cesium carbonate were added. The mixture was reacted at 65 °C for 15 h. The mixture was cooled to room temperature, extracted with ethyl acetate and deionized water, and the organic phase was concentrated and dried to obtain maleic anhydride vinyl POSS.

[0051] (3) Add 5 g of graphene oxide and 110 mL of N,N-dimethylformamide into a reaction flask, ultrasonically disperse for 2 h, add 2 g of maleic anhydride olefinic POSS, react at 85 °C for 3 h, filter after the reaction, wash with ethanol, and freeze-dry to obtain olefinic graphene grafted POSS.

[0052] (4) 65 g of linear low-density polyethylene and 35 g of metallocene polyethylene were vacuum dried and placed in a high-speed mixer, 8 g of olefin-grafted graphene POSS, 1.2 g of antioxidant 1010 and 0.5 g of thermal stabilizer zinc stearate were added, and the mixture was evenly dispersed at a stirring speed of 1100 r / min and a temperature of 95° C. The mixture was placed in a twin-screw extruder with a feed inlet temperature of 100° C., a front section temperature of 135° C., a middle section temperature of 150° C., a rear section temperature of 165° C. and a die head temperature of 170° C. for melt extrusion granulation, and then placed in a film blowing machine for blow molding to obtain an impact-resistant and highly wear-resistant PE film.

[0053] Example 5

[0054] (1) Under nitrogen atmosphere, 28 mmol of diamine POSS, 60 mmol of trans-4-hydroxycinnamic acid and 158 mL of N,N-dimethylformamide were added to a reaction flask. After stirring, 65.8 mmol of 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride, 47 mmol of 1-hydroxybenzotriazole and 90 mmol of triethylamine were added. The mixture was reacted at 95 °C for 15 h. Dichloromethane and deionized water were added for extraction. The organic phase was concentrated and dried to obtain diol vinyl POSS.

[0055] (2) Under nitrogen atmosphere, 22 mmol of diol vinyl POSS and 295 mL of N-methylpyrrolidone were added to a reaction flask. After stirring, 50 mol of 4-bromophthalic anhydride and 58.5 mmol of cesium carbonate were added. The mixture was reacted at 65 °C for 16 h. The mixture was cooled to room temperature, extracted with ethyl acetate and deionized water, and the organic phase was concentrated and dried to obtain maleic anhydride vinyl POSS.

[0056] (3) Add 10 g of graphene oxide and 235 mL of N,N-dimethylformamide into a reaction flask, ultrasonically disperse for 3 h, add 5 g of maleic anhydride olefinic POSS, react at 85 °C for 5 h, filter after the reaction, wash with ethanol, and freeze-dry to obtain olefinic graphene grafted POSS.

[0057] (4) 65 g of linear low-density polyethylene and 35 g of metallocene polyethylene were vacuum dried and placed in a high-speed mixer, 10 g of olefin-grafted graphene POSS, 1.2 g of antioxidant 1010 and 0.5 g of thermal stabilizer zinc stearate were added, and the mixture was uniformly dispersed at a stirring speed of 1050 r / min and a temperature of 100 ° C. The mixture was placed in a twin-screw extruder with a feed inlet temperature of 90 ° C, a front section temperature of 130 ° C, a middle section temperature of 145 ° C, a rear section temperature of 160 ° C, and a die head temperature of 180 ° C. The mixture was melt-extruded and granulated, and then placed in a film blowing machine for blow molding to obtain an impact-resistant and highly wear-resistant PE film.

[0058] Comparative Example 1

[0059] (1) Add 15 g of graphene oxide and 330 mL of N,N-dimethylformamide into a reaction flask, perform ultrasonic dispersion for 2 h, add 4.5 g of maleic anhydride, react at 80 °C for 4 h, filter after the reaction, wash with ethanol, and freeze-dry to obtain olefinic graphene.

[0060] (2) 80 g of linear low-density polyethylene and 20 g of metallocene polyethylene were vacuum dried and placed in a high-speed mixer, 2 g of olefinic graphene, 1.2 g of antioxidant 1010 and 0.5 g of thermal stabilizer zinc stearate were added, and the mixture was evenly dispersed at a stirring speed of 1000 r / min and a temperature of 95°C. The mixture was placed in a twin-screw extruder with a feed inlet temperature of 95°C, a front section temperature of 135°C, a middle section temperature of 145°C, a rear section temperature of 165°C, and a die head temperature of 170°C for melt extrusion granulation, and then placed in a film blowing machine for blow molding to obtain an impact-resistant PE film.

[0061] Comparative Example 2

[0062] 80g of linear low-density polyethylene and 20g of metallocene polyethylene were vacuum-dried and placed in a high-speed mixer, 2g of glycol olefinic POSS (prepared by Example 1), 1.2g of antioxidant 1010 and 0.5g of thermal stabilizer zinc stearate were added, and the mixture was evenly dispersed at a stirring speed of 1000r / min and a temperature of 95°C. The mixture was placed in a twin-screw extruder with a feed inlet temperature of 95°C, a front section temperature of 135°C, a middle section temperature of 145°C, a rear section temperature of 165°C, and a die head temperature of 170°C for melt extrusion granulation, and then placed in a film blowing machine for blow molding to obtain a highly wear-resistant PE film.

[0063] Comparative Example 3

[0064] 80g of linear low-density polyethylene and 20g of metallocene polyethylene were vacuum dried and placed in a high-speed mixer, 1.2g of antioxidant 1010 and 0.5g of heat stabilizer zinc stearate were added, and the mixture was evenly dispersed at a stirring speed of 1000r / min and a temperature of 95°C. The mixture was placed in a twin-screw extruder with a feed inlet temperature of 95°C, a front section temperature of 135°C, a middle section temperature of 145°C, a rear section temperature of 165°C, and a die head temperature of 170°C for melt extrusion granulation, and then placed in a film blowing machine for blow molding to obtain a PE film.

[0065] Abrasion test: The test was conducted in accordance with GB / T 5478-2008 standard. The prepared PE film was cut into thin strips and glued to the roller of the friction tester. It was first rolled at 0° for 600 circles for pre-wear and weighed. Then the angle was adjusted to 15° and rolled for 3416 circles. The weight after rolling friction was weighed and the abrasion was calculated to evaluate the wear resistance of the PE film.

[0066] Friction coefficient test: According to the method of GB / T 10006-2021, a friction coefficient meter is used, and the weight of the slider is 200g.

[0067] Table 1 Wear resistance test

[0068] Wear amount (mg) Friction coefficient Example 1 22.6 0.43 Example 2 15.2 0.32 Example 3 10.1 0.25 Example 4 6.5 0.19 Example 5 5.8 0.17 Comparative Example 1 34.5 0.63 Comparative Example 2 23.0 0.44 Comparative Example 3 58.1 0.75

[0069] As can be seen from the test results in the upper table, along with the increase of alkenyl graphene grafted POSS content, under the same friction pair rolling friction, through 3416 circles of about 1.61km of friction, the wear resistance of PE film gradually strengthens; Wherein the abrasion amount of embodiment 5 is only 5.8mg, and the wear coefficient is 0.17, this is because the alkenyl of alkenyl graphene grafted POSS can produce grafting reaction with polyethylene matrix, improves the compatibility between the two, avoids a large amount of agglomeration of inorganic particles, makes it uniformly dispersed in PE matrix; Simultaneously, the rigid inorganic cage-like core constituted by the silicon oxygen bond in POSS structure has higher hardness, can effectively resist the scratching and wear of the outside world, keeps the flatness and smoothness of the material surface, makes the PE film surface can form a stable lubricating film when being rubbed, thereby reduces the amount of wear, improves wear resistance. Comparative example 1 does not contain POSS structure, but contains graphene structure, and its wear resistance effect is not as good as the effect produced by POSS and graphene synergy; Comparative example 3 is pure PE film, and the amount of wear is relatively large, which limits the further application of PE film.

[0070] Dart impact strength test: Referring to GB9639-1988 standard, a dart impact tester is used to test the impact strength of the prepared PE film at a given height and under the impact of a free falling dart.

[0071] Tensile strength test: refer to GB / T 1040.3-2006 standard, use universal testing machine for testing, the tensile rate is 500mm / min, test 5 times and take the average value.

[0072] Table 2 Mechanical properties test

[0073]

[0074] As shown in the above table test result, along with the increase of alkenyl graphene grafting POSS content, the mechanical property of PE film strengthens gradually, wherein the dart impact strength in embodiment 4 is 1.95J, and tensile strength reaches 32.4MPa, this is because the graphene itself in alkenyl graphene grafting POSS has good mechanical property, when the anhydride group of maleic anhydride alkenyl POSS and the oxygen-containing group of graphene oxide esterification reaction, by chemical bond grafting to the surface of graphene, the graphene interlamellar spacing is propped up, effectively avoid mutually stacking, so that graphene is well dispersed in PE matrix, when impacted, the honeycomb structure of graphene can further attenuate impact force, with the expansion and extension of constraint microcrack, absorb energy, reduce the stress concentration of PE matrix, can better keep the stability of structure. Graphene is not contained in comparative example 2 and comparative example 3, can not effectively resist external impact, but contains POSS group in comparative example 2, its rigid structure gives the flexibility of PE film organic material and the hardness of inorganic material, and mechanical property is better than comparative example 3.

[0075] Antistatic performance test: Referring to the standard GB / T 1410-2006, the surface resistivity of the sample was measured using a high insulation resistance meter.

[0076] Table 3 Antistatic performance test

[0077] Surface resistivity(Ω) Example 1 <![CDATA[6.8×10 9 ]]> Example 2 <![CDATA[3.2×10 8 ]]> Example 3 <![CDATA[1.5×10 7 ]]> Example 4 <![CDATA[4.6×10 6 ]]> Example 5 <![CDATA[2.3×10 6 ]]> Comparative Example 1 <![CDATA[7.1×10 9 ]]> Comparative Example 2 - Comparative Example 3 -

[0078] Graphene oxide can chemically bond with the maleic anhydride group of maleic anhydride olefinic POSS and cross-link with polyethylene through the olefinic group in its structure. The increase in the degree of cross-linking allows graphene to adhere to the veins of the cross-linked network, forming a relatively complete graphene conductive pathway, improving the interface compatibility and enhancing the antistatic properties of the PE film. At the same time, the lamellar structure of graphene has good dispersion in the PE matrix, resulting in the obstruction of the path of water molecules or other pollutants through the PE film, thereby improving the barrier properties of the PE film.

[0079] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited to the specific details in the above embodiments. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, and these simple modifications all belong to the protection scope of the present invention. It should also be noted that the various specific technical features described in the above specific embodiments can be combined in any suitable manner without contradiction. In order to avoid unnecessary repetition, the present invention will not further describe various possible combinations.

Claims

1. A method for preparing an impact-resistant and highly wear-resistant PE film, characterized in that: The preparation method is carried out according to the following steps: Step (1), adding graphene oxide and N,N-dimethylformamide into a reaction flask, ultrasonically dispersing for 1-3 hours, adding maleic anhydride olefinic POSS, reacting at 75-90° C. for 2-5 hours, filtering after the reaction, washing with ethanol, and freeze-drying to obtain olefinic graphene grafted POSS; Step (2), vacuum-drying the linear low-density polyethylene and the metallocene polyethylene and placing them in a high-speed mixer, adding olefinic graphene grafted POSS, an antioxidant and a thermal stabilizer, and evenly dispersing them at a stirring speed of 800-1200 r / min and a temperature of 85-100° C., placing them in a twin-screw extruder, performing melt extrusion granulation, and then placing them in a film blowing machine for blow molding to obtain an impact-resistant and highly wear-resistant PE film.

2. The method for preparing the impact-resistant and highly wear-resistant PE film according to claim 1, characterized in that: In the step (1), the mass ratio of graphene oxide to maleic anhydride-based POSS is 100:(30-50).

3. The method for preparing the impact-resistant and highly wear-resistant PE film according to claim 1, characterized in that: In the step (2), the mass ratio of linear low-density polyethylene, metallocene polyethylene, and olefinic graphene-grafted POSS is (65-80):(20-35):(2-10).

4. The method for preparing the impact-resistant and highly wear-resistant PE film according to claim 1, characterized in that: In the step (2), the feed port temperature of the twin-screw extruder is 90-100°C, the front section temperature is 130-140°C, the middle section temperature is 140-150°C, the rear section temperature is 160-170°C, and the die head temperature is 160-180°C.

5. The method for preparing the impact-resistant and highly wear-resistant PE film according to claim 1, characterized in that: The preparation method of maleic anhydride alkenyl POSS in the step (1) is carried out according to the following steps: Step S1, under a nitrogen atmosphere, add diamine POSS, trans-4-hydroxycinnamic acid and N,N-dimethylformamide to a reaction flask, stir evenly, add 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride, 1-hydroxybenzotriazole and triethylamine, stir to react, add dichloromethane and deionized water to extract after the reaction is completed, concentrate the organic phase, and dry to obtain diol alkenyl POSS; Step S2, under a nitrogen atmosphere, add diol alkenyl POSS and N-methylpyrrolidone to a reaction flask, stir evenly, add 4-bromophthalic anhydride and cesium carbonate, stir to react, after the reaction is completed, cool to room temperature, extract with ethyl acetate and deionized water, concentrate the organic phase, and dry to obtain maleic anhydride alkenyl POSS.

6. The method for preparing the impact-resistant and highly wear-resistant PE film according to claim 5, characterized in that: In the step S1, the molar ratio of the diamine POSS, trans-4-hydroxycinnamic acid, 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride, 1-hydroxybenzotriazole and triethylamine is 1:(2.05-2.2):(2.1-2.4):(1.5-1.8):(3.1-3.3).

7. The method for preparing the impact-resistant and highly wear-resistant PE film according to claim 5, characterized in that: In step S1, the reaction temperature is 80-100° C. and the reaction time is 12-24 hours.

8. The method for preparing the impact-resistant and highly wear-resistant PE film according to claim 5, characterized in that: In the step S2, the molar ratio of diol alkenyl POSS, 4-bromophthalic anhydride and cesium carbonate is 1:(2.15-2.3):(2.5-2.8).

9. The method for preparing the impact-resistant and highly wear-resistant PE film according to claim 5, characterized in that: In step S2, the reaction temperature is 55-70° C. and the reaction time is 8-16 h.

Citation Information

Patent Citations

  • High toughness and impact resistant PE film and preparation method thereof

    CN107987360A